CIBSE guidance note : domestic hot water temperatures from instantaneous heat interface units (Chartered Institution of Building Services Engineers, 2021)
The impact of domestic hot water on energy efficiency is a relatively unexplored subject. Historically, domestic hot water has represented a relatively low percentage of building heat energy demand and has been supplied largely via cheap combustion heat sources. In the context of the climate emergency, and a move to lower carbon building designs, we have seen space heating energy requirements fall significantly. This means that domestic hot water now represents an increasingly significant percentage of total building energy consumption. However, the design requirements for domestic hot water are inconsistently understood and applied, particularly in low volume instantaneous hot water systems. This is exacerbated by disparate sources of guidance providing conflicting advice, in terms of both function and safety. There is a clear opportunity to develop a consistent approach to the design of these systems. This approach should prioritise function and safety, but also support low-carbon building design.
Keywords: Hot-water heating.; Hot-water heating -- Equipment and supplies.; elektronické knihy; electronic books